Risiko Diabetes Melitus Tipe 2 pada Mahasiswa Keperawatan dalam Perspektif Kesehatan Masyarakat - Fina Mahardini; Sudiro Sudiro; Sunarto Sunarto (Politeknik Kesehatan Kemenkes Surakarta, 2025)
Background: Type 2 diabetes mellitus (T2DM) is a global public health problem with an increasing prevalence among young adults. Nursing students, as future health professionals, have a strategic role in T2DM prevention; therefore, assessing their risk from a public health perspective is essential. Objectives: This study aimed to evaluate the risk of T2DM among nursing students and to compare the risk between early- and final-year students. Methods: A cross-sectional design was employed involving 114 respondents equally divided into two groups. T2DM risk was assessed using the Finnish Diabetes Risk Score (FINDRISC). Data were analyzed using the Mann–Whitney test. Results: The results showed that the mean T2DM risk score among early-year students was 4.16 ± 2.67, while among final-year students it was 3.96 ± 3.05 (p = 0.494), indicating no significant difference between the groups. Most respondents were classified as having a low risk. Conclusion: These findings suggest that T2DM risk among nursing students is relatively low and homogeneous, highlighting the importance of early risk screening, healthy lifestyle education, and promotive–preventive interventions as part of public health strategies. Keywords: Diabetes risk, FINDRISC, Nursing students, Public health, Type 2 diabetes mellitus